"Alternativas de emprendimientos de los migrantes retornados para el desarrollo de PYMES Turísticas en el cantón Chunchi". - Yamasqui Castillo, Inés (2016)
The purpose of this research is to design a technical assistance manual of tourism SMEs to guide local development through entrepreneurship strategies for the returned migrants of the Chunchi canton. This study segment has economic factor for the development of tourism SMEs; indicator which motivated this research, moreover the Canton has a clear opportunity for the development by taking as main opportunity its tourist attractions, strategic location, natural and cultural richness, which make this investigative work important for knowing what the existing entrepreneurship alternatives are and to identify the most important host according to the requirements of domestic and foreign tourists. Therefore it is worked according to the needs presented by returned migrants to invest in tourism SMEs by achieving benefits for returned migrants and other stakeholders than may participate in such information. To obtain results, it was employed several studies such as: Diagnosis of the current situation to know the alternatives of entrepreneurship and undertakings made in the canton, in this research several obtained documents were utilized in the house of the migrant in the province of Chimborazo (MIRECH), in addition, it was useful the information provided by The Decentralized Autonomous Government of Chunchi Canton as well as the returned migrants. SWOT analysis to get to know the strengths, weaknesses, opportunities and threats posed by returned migrants of the Chunchi Canton regarding the entrepreneurship alternatives, based on the identified weaknesses which indicated the importance of the proposed technical assistance. Manual of technical assistance to strengthen the alternatives of entrepreneurship in returned migrants, by being a tool guide basis for the development of tourism SMEs in the canton improving the entrepreneurial attitude and encouraging initiative, training and advice on entrepreneurship and strategies to undertake them.